The Effectiveness Of Cognitive Restructuring Techniques In Group Counseling Services To Reduce Online Learning Burnout In College Students - Apriliya, Pradana; Lianawati, Ayong (Universitas Mathla'ul Anwar Banten, 2023)
This research was conducted to measure the effectiveness of cognitive restructuring techniques of group counseling services to reduce online learning burnout in BK UNIPA Surabaya students. The design used is a one-group pre-test post-test with a target of 6 students who have a high level of online learning saturation obtained from the pre-test questionnaire scores. This research is classified as quantitative research using non-parametric analysis with the Wilcoxon test. The result of this research is Asymp value. Sig (2-tailed) of 0.012. Value is smaller than 0.05, so it can be concluded that Ho is rejected and Ha is accepted. The final results of the post-test scores given to the six students showed a decrease in learning saturation scores from the six students in the high category to the low category. So the results of this research read that cognitive restructuring techniques have a significant effect in group counseling services to reduce online learning boredom in BK UNIPA Surabaya college.